Assembly technology and design features of microelectronic coordinate-sensitive detectors - Sidorenko, V. P.; Zhora, V. D.; Radkevich, O. I.; Grunyanska, V. P.; Prokofiev, Yu. V.; Tayakin, Yu. V.; Virozub, Т. М. (Technology and design in electronic equipment, 2018)
The design features and assembly technology of microelectronic coordinate-sensitive detectors of charged particles for spectroscopy are considered. The device is based on the specialized very-large-scale integration (VLSI) crystal manufactured using CMOS technology and containing a charge-sensitive matrix designed to detect isotope ions in a wide mass spectrum of the test substance. The range of concentrations measured by devices is also wide and ranges from 10–7 to 100%. The VLSI crystal is placed on a multilayer ceramic basis. The devices also contain a Hamamatsu micro-channel plate (MCP), electrodes that supply high voltage to integrated circuits (2.0 kV), a non-magnetic metal shield for protecting the device components, a connector and other structural elements.VLSI crystals are installed using the method of laying the microcircuits on a flexible aluminum — polyimide media. Such mounting method has a number of advantages over others. The VLSI crystals with project standards of 1 μm are designed for the possibility to create new generation of detectors, which can include either one or several crystals. The prototype version has been developed, and it allows placing a bar of five ceramic-based crystals with a minimum gap of 100 μm between them. This design provides high reliability of products due to the usage of multilayer ceramic boards and due to progressive assembly methods used in the manufacturing of special-purpose microelectronic equipment, including the equipment resistant to special external factors.